Habits of consumption and environmental impact: how the consumer handles with the consumption requirements of everyday life - Ferreira, Maria Eloneide; Marsaro, Cecilia Cavalcante Silva; Valentini, Carla Maria Abido; Faria, Rozilaine Pelegrine Gomes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This work aimed to evaluate the socio-economic profile of economically active people aged between 18 and 30 years and the influence of advertising in relation to purchasing power taking into account the potential environmental impact caused by the bad habits of consumption . The research was conducted using a questionnaire structured with 11 objective questions and one subjective question. The income level, educational level, debts on income, level of representation in the purchase decision, advertising and which influences over purchasing activity that produces more residue. The majority (55%) of the respondents were female, had completed secondary education (28%), 59% have income range up to one monthly wage, 46% committed over 70% of their monthly income with debts. The price was the determining factor in the purchase decision for most respondents at different educational levels. All respondents, regardless of education level, cited food and shopping in supermarkets as activities that generate the greatest amount of residue after consumption. The advertising influences the buying decision in 73% of respondents. Younger individuals and with low educational level individuals need to undertake a portion of their income on the purchase of basic items for survival, end up compromising much of the income with basic expenses. Educational campaigns focused on natural resource economics could be used reducing the environmental impact generated by the overconsumption.